2020
DOI: 10.1108/meq-03-2020-0059
|View full text |Cite
|
Sign up to set email alerts
|

Selection of sustainable transport system: a case study

Abstract: PurposeSustainable mobility will be the key to the survival of mankind in the 21st century. Cities with debt-ridden and poorly managed transport systems have to change to the ever-growing demands of the public transport system. The low cost of transport has been a key factor in sustainable development for any city. This study is trying to propose a framework for the selection of sustainable transport in context to an Indian case of NCR Delhi, India.Design/methodology/approachThe present study has identified ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 49 publications
0
30
0
2
Order By: Relevance
“…Also, the CSR activities build the reputation of a firm. Previous studies have indicated that corporate reputation strengthened the linkage between CSR and performance (Lu et al , 2019; Irshad et al , 2017; Singh et al , 2020). Lu et al (2020) indicated that the reputation of an organization enhances the firm organizational performance.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 94%
“…Also, the CSR activities build the reputation of a firm. Previous studies have indicated that corporate reputation strengthened the linkage between CSR and performance (Lu et al , 2019; Irshad et al , 2017; Singh et al , 2020). Lu et al (2020) indicated that the reputation of an organization enhances the firm organizational performance.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 94%
“…Zagorskas and Turskis [122] proposes a fuzzy-based methodology that allows policy makers to rank the priorities for development and renewal of bicycle pathway segments. Based on a case study in a large Indian city, Singh et al [123] introduce a framework for the selection of sustainable transport. Different transportation alternatives are considered: state-run bus, pooled car, and private buses.…”
Section: Applications Of Fuzzy Sets To Sustainable Transportation Systemsmentioning
confidence: 99%
“…Sustainability as a concept took its roots in 1987 and proposed by the World Commission on Environment and Development (WECD) (Singh, Gurtu, & Singh, 2020). In this initial definition, the emphasis was put on the continuity of and responsibly use of the environmental and natural resources while considering the forthcoming generations (Küçükoğlu & Pınar, 2018).…”
Section: Introductionmentioning
confidence: 99%